Horticultural Characteristics of Summer Apple Cultivars from Turkey - Kerem Mertoğlu; Emre Akkurt; Yasemin Evrenosoğlu; Ayşen Melda Çolak; Tuba Esatbeyoglu (Plants, 2022)
Early varieties with a short active vegetation period are not exposed to abiotic stress factors for instance drought, high temperature, etc., caused by global climate change, and biotic stress factors such as codling moth (Cydia pomonella) and apple scab (Venturia inequalis) that cause serious economic losses. Therefore, their places are extremely important regarding sustainable, economical and quality production. In this context, four early varieties of apple (‘Vista Bella’, ‘Summer Red’, ‘Williams Pride’ and ‘Jersey Mac’) grown in Eskisehir—Turkey where has continental climate were characterized in terms of horticultural characteristics. The difference observed in flowering and harvest times between years showed that average air temperatures are essential on phenological characteristics. Furthermore, high temperature accelerates development physiology of fruit. Major important characteristics, namely, fruit length, width, weight, soluble solid content, antioxidant activity, vitamin C and total phenolic content were found in the range of 39.19–50.88 mm, 51.48–60.81 mm, 80.59–86.16 g, 11.87–12.19%, 50.69–80.57%, 2.24–4.79 mg 100 mL−1 and 259.23–871.42 mg GAE (gallic acid equivalent) L−1, respectively. ‘Summer Red’ and ‘Williams Pride’ varieties were found to be good in terms of pomological characteristics, while ‘Vista Bella’ came to the fore with its chemical properties. On the other hand, ‘Jersey Mac’ has shown superior performance in terms of both pomological and chemical characteristics. Pomological characteristics are affected more by ecological differences, while chemical characteristics vary according to the changes in the pomological properties. Pomological characteristics were found to have a significant positive correlation with each other but negatively correlated with chemical characteristics.